First Soviet Contacts of Angelo Maria Ripellino (Documents from Russian State Archive of Literature and Art) - Anastasia V. Golubtsova (Литературный факт)
The article is dedicated to the first Soviet contacts of Italian philologist Angelo Maria Ripellino, researcher and translator of Russian and Soviet literature. The article studies the beginning of his long correspondence and friendship with translator Georgij Breitburd and poet Alexey Surkov and his first visit to the USSR in 1957. Documents from Russian State Archive of Literature and Art (RGALI) help us understand how the Soviet part supported Ripellino’s research and edition projects: they provided illustrations for his study on Mayakovsky, sent him poetry books and information about the authors for an Italian edition of contemporary Soviet poets, and helped to organize his trip to Moscow. In 1957, Ripellino also took part in a meeting of Soviet and Italian poets in Rome, organized by the Italy-USSR Association. The article pays special attention to Ripellino’s contacts with Boris Pasternak and to his work on the anthology New Soviet Poets (1961), and examines the role of the Soviet part in it. As a supplement to the article we publish some of the documents from RGALI providing important information about Ripellino’s Soviet contacts. It is correspondence with Soviet writers and a transcript of an interview given to Georgij Brejtburd in Moscow, in which Ripellino discusses his future book Mayakovsky and Russian Avant-Garde Theatre, the popularity of Soviet poetry in Italy, and the meeting of Soviet and Italian poets in Rome planned for October 1957. We provide the documents with a comprehensive commentary using information from Soviet and Italian press (Pravda, Literaturnaya Gazeta, L’Unità).